DV–hop node localisation algorithm with multi–mobile beacons in wireless sensor networks. (1st January 2015) - He, Wenxiu; Wang, Xianbao; Chen, Defu
This paper proposes a node localisation algorithm with multi–mobile beacons in order to improve the accuracy of localisation and avoid scanning the unknown nodes repeatedly. Three mobile beacons are designed to traverse the WSNs and simultaneously maintain the relative location relations between them based on equal distance three–coverage and then trilateration technology and DV–hop algorithm are used to localise the unknown nodes. The simulation results show that the algorithm outperforms DV–hop and MB–DV–hop in the aspects of accuracy and communication overhead and its moving path length of single beacon is also shorter than that of MB–DV–hop.